Open Warfare against the Effeminate Boy: a Queer Auto-ethnography - Cornejo, Giancarlo (2011)
How does one become aware of oneself? How does one become aware of the vulnerability that constitutes one´s own identity? These are the words that inspire the development of a self-ethnography through which the author problematizes his own place of enunciation in order to respond to the homophobic questioning he was subjected to as a child. It is an exercise in recovering his own history marked by violent exclusions, domination and subjugation, in order to become aware of the way the heterosexual norm acts on the subjectivities of effeminate subjects. For the author it is a problematization of his own experience of vulnerability and shame and historicity which opens the possibility of re-signification, reparation and subversion, principles which allow us to live as we wish to.